PEMAGANGAN LUAR NEGERI TENAGA KERJA: PROSES, PENDAPATAN, DAN ALIH TEKNOLOGI - Agus Joko Pitoyo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
This study is aimed to investigate the mechanism of abroad apprenticeship labour program, including income rate, to understand the process of transferring knowledge, and to portray its implementation to regional development. There are at least three aspects will be discussed, firstly, to understand the process of apprenticeship overseas; secondly, to evaluate their income and economic activities after returning home; and thirdly, to evaluate how the local government involves in empowering ex-apprentice labour overseas. The research employed several methods for getting data such as structured interview by using questionnaire, focus group discussion, in-depth interview, tracking, and observation. This study indicated that (I) Apprenticeship process mechanism is not fully transparent yet; (2) Their income are relatively high, however, looking at their job they are still absorbed in 3D jobs (dirty, dangerous, difficult); (3) Several arising problems set the volunteer in low bidding position, and (4) process of transferring knowledge they got from overseas is vague.